Kinetic and Isotherm Studies of the Adsorption Phenacetin onto Two Copper Porous Coordination Compounds: Nonlinear Regression Analysis - Djoumbissie Alvine Loris; Tchuifon Tchuifon Donald Raoul; Atemkeng Donlifack Cyrille; Kuete Tiotsop Idris-Hermann; Doungmo Giscard; Tayo Djampouo Alain Clovis; Anagho Solomon Gabche; Ngoune Jean (Journal of Chemistry)
Two coordination compounds, copper (II) fumarate (CuFum) and copper (II) tartrate (CuTart), synthesized from copper (II) with fumaric acid and tartaric acid as ligands and using the slow evaporation method have been applied to study the adsorption of phenacetin in aqueous solution. These compounds were characterized by elemental analysis, IR-FT spectroscopy, and X-ray powder diffraction. The melting points of the synthesized coordination compounds were found to be above 350°C. The influence of parameters such as the initial pH, the contact time, and the initial concentration on the adsorption of phenacetin in an aqueous solution has been studied. The studies showed that adsorption equilibrium was reached after 80 minutes for both coordination compounds; the adsorption capacity increased with increasing phenacetin concentration, and the maximum adsorption capacity was obtained in the acidic medium at pH 4. The adsorbed amount of phenacetin on copper (II) fumarate (CuFum) was 25.158 mg/g while that on copper (II) tartrate (CuTart) was 25.906 mg/g. Nonlinear regression analysis showed the best fit for the Freundlich model isotherm for CuTart with R2 of 0.963 and a Chi-square test (χ2) of 0.529 while for the CuFum material, it is the Redlich-Peterson model with R2 of 0.975 and Chi-square test (χ2) of 0.263. The kinetic study shows that the pseudo-second-order model better describes the adsorption of the two materials. The results show that physisorption and chemisorption participate in the adsorption of phenacetin and that these materials can be used for the elimination of phenacetin in solution.